2018
DOI: 10.1002/ab.21773
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol intoxication and sexual interest on men's sexual persistence and hostility in a dating simulation

Abstract: Perpetrators of sexual assault are often intoxicated; however, few experimental studies evaluate alcohol's "in the moment" effects on sexual aggression. This study extends past theory and research by examining the acute effects of alcohol on men's decisions about how to respond to sexual refusals in a dating simulation. Men (N = 62) ages 21-29 were randomly assigned to consume alcohol (target breath alcohol level 0.080%) or no alcohol. Participants were encouraged to talk to a simulated woman and act as they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…We hypothesized that heavy episodic drinking might similarly mediate sexual coercion because alcohol use impairs women’s ability to detect and respond effectively to risk in sexual scenarios, leaving them more susceptible to experiencing sexual coercion. Alcohol use also contributes to men’s misperceptions of women’s nonsexual cues as sexual (Abbey et al, 2005) and persistence in the face of women’s refusal (Woerner et al, 2018). We hypothesized that these effects might be enhanced within hookups, which are predicated on a lack of familiarity or agreement on what will occur (e.g., Garcia & Reiber, 2008), thereby being opportune settings for coercion to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that heavy episodic drinking might similarly mediate sexual coercion because alcohol use impairs women’s ability to detect and respond effectively to risk in sexual scenarios, leaving them more susceptible to experiencing sexual coercion. Alcohol use also contributes to men’s misperceptions of women’s nonsexual cues as sexual (Abbey et al, 2005) and persistence in the face of women’s refusal (Woerner et al, 2018). We hypothesized that these effects might be enhanced within hookups, which are predicated on a lack of familiarity or agreement on what will occur (e.g., Garcia & Reiber, 2008), thereby being opportune settings for coercion to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol intoxication is thought to contribute to assault risk through several mechanisms (see review: Melkonian & Ham, 2018). Alcohol consumption acutely impairs women’s ability to recognize and respond to risk in sexual scenarios (Parks, Levonyan-Radloff, Dearing, Hequembourg, & Testa, 2016; Testa, VanZile-Tamsen, Livingston, & Buddie, 2006) while impairing men’s ability to attend to women’s cues of disinterest (Abbey, Zawacki, & Buck, 2005) or to desist when women overtly refuse their advances (Woerner, Abbey, Pegram, & Helmers, 2018). Using a virtual reality paradigm, Woerner et al (2018) found that men who engaged in more lower level consensual sexual activity (e.g., touching) with a woman were more likely to persist in the face of her sexual refusals.…”
mentioning
confidence: 99%
“…Specifically, the fact that alcohol use is clearly linked with perpetration is somehow undermined by the belief that victims share the blame if they too are intoxicated (e.g., Hunt et al, 2021; James-Hawkins & Lamarche, forthcoming). Furthermore, in much of the extant survey research on this topic, it is difficult to separate alcohol use by the victim/perpetrator because both parties are often drinking (e.g., Zawacki et al, 2003; Pegram et al, 2018; Woerner et al, 2018). The current research addresses these methodological limitations by explicitly quantifying alcohol consumption, as well as whether quantities were matched or unmatched between partners, across scenarios.…”
Section: Current Researchmentioning
confidence: 99%
“…Alcohol is a robust predictor of sexual assault perpetration (Abbey, 2011). Individuals report greater sexual assault behaviors and intentions when intoxicated compared to when sober (Abbey, 2011; Shorey et al, 2014; Testa et al, 2019; Woerner et al, 2018). The association between acute intoxication and sexual assault perpetration may be explained by alcohol’s deleterious effects on information processing (e.g., alcohol myopia theory [AMT]).…”
Section: Alcohol As a Predictor Of Sexual Aggressionmentioning
confidence: 99%